The WTO Primer: Tracing Trade's Visible Hand Through Case Studies - Buterbaugh, Kevin; Fulton, Richard M. (Palgrave Macmillan, 2008)
Keywords: 20th century; 20th century; Commercial policy; History; History; General Agreement on Tariffs and Trade (Organization); History; International trade; World Trade Organization; dept.psc

Trade and the Environment - Buterbaugh, Kevin (Encyclopedia of Violence, Peace, & Conflict (Second Edition), 2008)
This article examines the debate over the compatibility of trade and the environment. First, it discusses the range of arguments in the debate from trade being inherently beneficial to inherently harmful to the environment. Second, the entry examines the place of the environment within the GATT/WTO and various controversies surrounding the GATT/WTO and environmental protection. Finally, the article examines the role of multilateral environmental agreements in protecting the environment and their possible consequences for the international trading system.
Keywords: Eco-labeling; Environmental Kuznets curve; Environmental dumping; Environmental externality; Free-rider problem; GATT/WTO; Harmonization of standards; Multilateral environmental agreements; Precautionary principle; Race to the bottom; Sanitary and phytosanitary agreement; Technical barriers to trade agreement; Trade-environment debate; Trade–environment debate; dept.psc

Aristocratic and confederate republicanism in Hamiltonian thought and practice - O'Hara, Jonathan (Publius-the Journal of Federalism, 2008)
This article identifies and explores the presence of republican thought in the intellectual and policy writings of Alexander Hamilton, particularly as it applied to his theoretical understanding of the American executive branch. The article moves chronothematically, highlighting, through the Revolutionary, Constitutional, and Governmental periods of American political development, Hamilton's unique sense of republicanism with respect to international and domestic politics, as well as American political economy. The article not only attempts to demonstrate Hamilton's intellectual adherence to the republican tradition, but also his commitment to rhetorically applying the ideology to the realization of practical executive policy goals.
Keywords: dept.psc